O’ZBEKISTONNING JANUBIY HUDUDLARIDA TARQALGAN RODENTIA TURKUMINING TABIATDAGI AHAMIYATI - Tursunov O. T., Tursunov O. T. (Actual problems and prospects of the study of the fauna, 2024)
In this article, the ecological status of the Rodentia family distributed in Uzbekistan, its importance, and the relationships between representatives of other families are presented. The information about the place of representatives of the category in nature, the fact that they are an integral part of biological diversity and an integral part of biological relations is presented.